Project for the new Nordelta station of the Miter Line in the Tigre district: Notes for a socio-urban evaluation of railway Intermodal nodes (Desarrollo, Estado y Espacio, 2023)
The Sustainable Mobility Plans produced in recent decades have strengthened the role of public transport, marking the rail-guided mode as more efficient in energy and environmental terms compared to self-transported modes. The stations operate as nodes in the relationship with the local urban community, allowing connectivity and accessibility, and simultaneously irradiating commercial economic activity in their immediate surroundings. It is essential to analyze this articulation between mobility infrastructure and local development with some of the terms, concepts and keywords proposed in Development Oriented to Sustainable Transport (DOTS), a line of global public policies that finances improvements to railway centers transfer.Our starting point seeks to investigate the complex relationships between the planning of transport infrastructures -in this case railways- and the urbanization processes deployed from various expansion or concentration strategies on a metropolitan scale. In this article, we seek to investigate possible urban and regional development strategies, where mobility plays a leading role in the production of urban space, which is why we propose to evaluate transport projects within the framework of the sustainable mobility paradigm and in socio-urban key.As a case study, we take the project for the construction of a new railway station between the General Pacheco and Benavides stations of the Miter branch Villa Ballester-Zárate line, which will be located from the street of the Talar del Lago tunnel and parallel to the Bancalari-Benavidez corridor. , having its median axis of platforms on Progressive 35+400 with respect to Retiro station, in the Autonomous City of Buenos Aires, head of the service. The location allows us to reflect on the socio-environmental contrasts resulting from the interrelationship between the gated communities of Nordelta, the city built between the tracks and the former national route 9, current Presidente Perón avenue, the logistics enclaves in the northern area of the Buenos Aires Metropolitan Region. Aires and the settlements that emerged in the courses of the streams and interstitial spaces, where poverty and wealth fragment an increasingly unequal urbanization.The objective of the project is to serve to "satisfy the demand of the neighborhoods in the area in which it will be implemented, providing significant improvements in accessibility, and will constitute a starting point for the generation of a new urban enclave of a social nature. and commercial that will strengthen the area" (ADIFSE IF-2022-54929969-APN-IPE#PE, page 17). The guiding question of the analysis arises from contrasting the immediate environment of the station with the dimensions and indicators that the DOTS initiatives propose to estimate its socio-urban behavior, identifying opportunities for improvement, social integration, and environmental protection.
Keywords: Railway infrastructure; Centralities; Sustainable mobility; Transport-oriented development